An analysis the utility data at high density area [Taman Selayang Jaya Selangor] for utility mapping purpose / Riezarman Ramli - Ramli, Riezarman (2022)
Due to the pressures of high density area, utility requirements such as water, electricity, and gas, as well as fibre optics, drainage, and sewage, will also increase. In the age of big data, the utility mapping data can be extremely beneficial for comprehending dense areas. The utility mapping of underground utility networks been used for land administration purposes. This study shows about explanation the implementation of high density area and analysis of underground utility at Taman Selayang Jaya, Selangor. The investigation of utility data has been proposed in order to manage the work process from data collection to data usage. Existing test data has been analysed to determine whether the area is suitable for pipes and cable renewal in high density areas. The case study integrates collected data from Pipe Cable Locating (PCL) and Ground Penetrating Radar (GPR) create a utility mapping. PCL and GPR has been found to be a non-destructive method for accurately and efficiently detecting pipes and cable in this study. For pipeline detection, PCL and GPR has proven to be an effective tool. The aim of this study is to explore, collect data, analysis, calculate and produce the output. To accomplish the aim, the objective of this research are to define the utility data using PCL for high density area, to organize the data obtain from utility survey for high density area using the suitable platform and to verify the utility mapping plan for high density area with appropriate analysis. Apart from that, the methodology is divided into four phases; phase 1 is the preliminary study, phase 2 is the data acquisition, phase 3 is the data processing phase, and phase 4 is the result and analysis. All phases has been completed in order to obtain the final result, which is analysis utility mapping.